A Cytokine Dynamics in Multiple Sclerosis: Modulating Adaptive Immunity in Neuroinflammation - Mualla, Yara; Alrahimi, Jehan (Journal of Biological Insights, 2026)
Multiple sclerosis (MS) is a chronic autoimmune disorder of the central nervous system (CNS) characterized by immune system dysfunction, inflammation, and demyelination. This review examines the intricate roles of cytokines in regulating neuroinflammation and influencing adaptive immune responses. Proinflammatory cytokines, including IL-6, IL-17, and IFNγ, drive pathological processes by promoting immune cell activation and tissue damage, while anti-inflammatory cytokines, such as IL-10 and IL-22, contribute to immune regulation and neuroprotection. Furthermore, the review explores the emerging role of novel cytokines in MS pathophysiology, shedding light on newly identified immune mediators and their implications for disease progression. By analyzing cytokine profiles and their interplay with adaptive immunity, we gain valuable insights into the immunopathogenic mechanisms underlying MS. This comprehensive examination aims to deepen our understanding of the cytokine-mediated dynamics in MS, offering potential biomarkers for disease activity and guiding future research directions. A literature search was conducted across multiple databases, including PubMed, NCBI, and MDPI, to identify studies relevant to the role of cytokines in MS and the involvement of adaptive immunity in the disease process. Articles were selected using predefined keywords such as cytokines, multiple sclerosis, and adaptive immunity.